The psychological impact on perioperative healthcare workers during Victoria's second COVID-19 wave: A prospective longitudinal thematic analysis. (March 2023) - Ku, Michelle; Ng, Irene; Barson, Elizabeth; Fisher, Caroline; Segal, Reny; Williams, Daryl Lindsay; Krieser, Roni Benjamin; Mezzavia, Paul Mario; Lee, Keat; Chen, Yinwei; Sindoni, Teresa; Withiel, Toni
The COVID-19 pandemic has had a profound psychological impact on our frontline healthcare workers. Throughout the entire second COVID-19 wave at one major tertiary hospital in Melbourne Australia, longitudinal qualitative data between perioperative staff members, and analyses of intrapersonal changes were reported. Inductive analysis of three open-ended questions generated four major themes: Organisational Response to the Pandemic, Psychological Impact, Changes in Feelings of Support Over Time and Suggestions for Changes. Understanding the challenges, perception and suggestions from this longitudinal study allows us to provide a range of support services and interventions to minimise the long-term negative psychological impact and be better prepared should another similar situation arises again.